Constraints on the Rheology of the Lithosphere From Flexure of the Pacific Plate at the Hawaiian Islands - Ashley Bellas; Shijie Zhong; Anthony Watts (Geochemistry, Geophysics, Geosystems, 2020)
Abstract The rheology of oceanic lithosphere is important to our understanding of mantle dynamics and to the emergence and manifestations of plate tectonics. Data from experimental rock mechanics suggest rheology is dominated by three different deformation mechanisms including frictional sliding, low‐temperature plasticity, and high‐temperature creep, from shallow depths at relatively cold temperatures to large depths at relatively high temperatures. However, low‐temperature plasticity is poorly understood. This study further constrains low‐temperature plasticity by comparing observations of flexure at the Hawaiian Islands to predictions from 3‐D viscoelastic loading models with a realistic lithospheric rheology of frictional sliding, low‐temperature plasticity, and high‐temperature creep. We find that previously untested flow laws significantly underpredict the amplitude and overpredict the wavelength of flexure at Hawaii. These flow laws can, however, reproduce observations if they are weakened by a modest reduction (25–40%) in the plastic activation energy. Lithospheric rheology is strongly temperature dependent, and so we explore uncertainties in the thermal structure with different conductive cooling models and convection simulations of plume‐lithosphere interactions. Convection simulations show that thermal erosion from a plume only perturbs the lithospheric temperature significantly at large depths so that when it is added to the thermal structure, it produces a small increase in deflection. In addition, defining the temperature profile by the cooling plate model produces only modest weakening relative to the cooling half‐space model. Therefore, variation of the thermal structure does not appear to be a viable means of bringing laboratory‐derived flow laws for low‐temperature plasticity into agreement with geophysical field observations and modeling.